Media Sosial Sebagai Sarana Membentuk Identitas Diri Mahasiswa Universitas Airlangga Surabaya - Dinda Marta Almas Zakirah (Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
Currently, technology does not only provide ease for the users but also creates some social media that makes the users be able communicating from distances. Social media can also be used to share any photos and videos such as the one that is being the favorite of its users namely instagram. However, instagram is no longer functions for photo and video sharing but to form self-image.Many youth try to build up their self-images on instagram and many of them are students of Airlangga University. Therefore, this research is conducted to know how students of Airlangga University form their self-images on instagram. This research uses qualitative approach. The data collection technique in this research is in-depth interview and field observation.The theories used in this research are hiperrealitas Jean Baudrillard andNet Generation Theoryfrom Don Tapscott. Then, the sampling uses purposive method. The subjects of this research are 8 students consisting female and male students of Airlangga Universitywho are included in two instagram accounts namely @satuunair and @unairhitspeople. The result of this research reveals that students of UNAIR form their self-images on instagram. They do it by editing the photo they will share on instagram, also the selection of location and angle for a photo. Besides, forming self-identity on social media does not fully give negative effect.By the internet and smart phones, the intensity to use smart phones gets bigger than before the internet existed. Hence, it proofs that they get positive beneficial impact. Keywords: University student, social media, instagram, self-image, net generation.